Fault analysis and performance improvement of grid-connected doubly fed induction generator through an enhanced crowbar protection scheme. - Rameez Akbar Talani; Ghulam Sarwar Kaloi; Aamir Ali; Ghulam Abbas; Ahmed Emara; Ezzeddine Touti (PLoS ONE)
The main problem associated with a doubly fed induction generator (DFIG) during fault is large inrush currents induced in rotor winding, which has detrimental effects on the machine's AC excitation converter. A simple conventional resistance inclusion (crowbar) is employed with a PI controller to protect a DFIG from transient current, but it is observed that this method is not enough to keep transient over-current to an admissible level. In this paper, an effective current limiting technique along with reactive power control is proposed in order to maintain stability, reduce transient current surge to an acceptable level, and enhance the Fault Ride Through capacity of DFIG. The proposed dynamic control technique not only limits the fault current during voltage dip to a permissible level but also controls the reactive power during fault. The behavior of a proposed technique is analyzed by introducing unsymmetrical faults in the MATLAB-based model of DFIG. An enhanced crowbar-based fault ride-through is employed for the rotor side controller to limit inrush current and control reactive power.